2023
DOI: 10.1021/acs.jpcc.3c03797
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Optical Properties of 2D CdSe Nanoplatelets in a Nonresonant Regime

Abstract: The nonlinear optical response of CdSe and CdSe/CdS core/shell nanoplatelets (NPLs) in toluene suspension was determined by using Z-scan and optical Kerr gate (OKG) techniques at 800 nm in the femtosecond regime. First, an analysis of the nonlinearities based on the Z-scan resulted in n 2 = 1.4 × 10 −16 cm 2 /W and n 2 = 1.3 × 10 −16 cm 2 /W for CdSe and CdSe/CdS core/shell NPLs, respectively. Fifth-order nonlinear absorption behavior was predominant, resulting in α 4 = 4.0 × 10 −2 cm/GW for CdSe NPLs and α 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…There are endless reports of determination of optical properties of different materials developed through different physical deposition techniques in thin film form. For instances, in the year 2023 only:-Vijay et al investigated the impact of annealing temperature on the microstructure, defects, and optical properties of ZnO thin films using a sol-gel-based spin coating method and showed that particle size increases with annealing temperature, and the optical band gap reduces [22]; Banerjee et al investigated the origin of visible emissions in ZnO, focusing on excitation wavelength-dependent tuneable emission [23]; Orek et al studied the electrical, optical, and structural properties of a wurtzite-like zinc oxide nanostructure, examining the influence of quantum confinement on optical characteristics [24]; Sarmh and Borah studied nanocrystalline CdSe thin films, finding them suitable for optoelectronic devices with defect-controlled photocurrents and a doubly activated transport mechanism [25]; Gonçalves et al studied the nonlinear optical response of CdSe, revealing a predominant fifth-order nonlinear absorption behaviour and a nonlinear refractive index in good agreement with the OKG [26]; Kafashan et al investigated the impact of Cu-doping on Cadmium selenide (CdSe), highlighting its potential applications in optoelectronics due to improved absorbance, reflectance, and band gap [27].…”
Section: Introductionmentioning
confidence: 99%
“…There are endless reports of determination of optical properties of different materials developed through different physical deposition techniques in thin film form. For instances, in the year 2023 only:-Vijay et al investigated the impact of annealing temperature on the microstructure, defects, and optical properties of ZnO thin films using a sol-gel-based spin coating method and showed that particle size increases with annealing temperature, and the optical band gap reduces [22]; Banerjee et al investigated the origin of visible emissions in ZnO, focusing on excitation wavelength-dependent tuneable emission [23]; Orek et al studied the electrical, optical, and structural properties of a wurtzite-like zinc oxide nanostructure, examining the influence of quantum confinement on optical characteristics [24]; Sarmh and Borah studied nanocrystalline CdSe thin films, finding them suitable for optoelectronic devices with defect-controlled photocurrents and a doubly activated transport mechanism [25]; Gonçalves et al studied the nonlinear optical response of CdSe, revealing a predominant fifth-order nonlinear absorption behaviour and a nonlinear refractive index in good agreement with the OKG [26]; Kafashan et al investigated the impact of Cu-doping on Cadmium selenide (CdSe), highlighting its potential applications in optoelectronics due to improved absorbance, reflectance, and band gap [27].…”
Section: Introductionmentioning
confidence: 99%